Kaji Numerik Pengkondisian Udara di Workshop Teknik Mesin Universitas Majalengka Menggunakan Autodesk Simulation CFD 2015 - Imam Mutaqin; Asep Rachmat; Yudi Samantha (PROCEEDING STIMA)
Good air circulation is needed in a room that has a high load to achieve thermal comfort. This study aims to assess the flow of air in the room as workshops Faculty of Mechanical Engineering at the University of Majalengka, in order to determine the amount of air conditioning needed, determine the spread of conditioned air to the room, and the location of the air conditioner in the room. This experimental research using CFD simulation (Computational Fluid Dynamics), input parameters in the simulation obtained through field measurements such as workshops dimensional space. The analysis was conducted to determine the portion of space that experienced high and low air flow.Keyword : Air Conditioner, simulation CFD, Heat Transfer